2017
DOI: 10.3168/jds.2017-12559
|View full text |Cite
|
Sign up to set email alerts
|

A method of outdoor housing dairy calves in pairs using individual calf hutches

Abstract: Interest in housing dairy calves in groups is currently growing. Group housing using individual calf hutches, a resource already available in most dairy farms in North America, could provide a novel housing method that can be a simple way to implement group housing on farm. The main objective of this study was to determine whether pair housing dairy calves in hutches outdoors would result in similar weight gain and milk intake compared with individual housing in hutches. The study was designed to avoid competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…In routine events are consistent, predictable, and not very diversified. While providing outdoor access permits animals to express greater socialization and natural behavior (21,22), it also means exposing them to initially unknown and diverse stimuli that could heed unforeseeable responses. The provisioning of various stimuli and so, enrichment, allows cows to develop a range of behaviors and reactions, and therefore, promotes the animal's capacities of adaptation (18).…”
Section: Discussionmentioning
confidence: 99%
“…In routine events are consistent, predictable, and not very diversified. While providing outdoor access permits animals to express greater socialization and natural behavior (21,22), it also means exposing them to initially unknown and diverse stimuli that could heed unforeseeable responses. The provisioning of various stimuli and so, enrichment, allows cows to develop a range of behaviors and reactions, and therefore, promotes the animal's capacities of adaptation (18).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of social housing on calf performance and behavior has received considerable attention (Jensen et al, 1997;De Paula Vieira et al, 2010), and recently interest has increased in using hutches to pair-house calves (Cobb et al, 2014;Pempek et al, 2016;Wormsbecher et al, 2017). Cobb et al (2014) reported improved performance in group-housed calves compared with individually housed calves, but their results may not apply to conditions on many commercial farms given that group hutches (2.26 × 2.69 m) were used.…”
mentioning
confidence: 99%
“…Beyond the social benefits of pair housing, this practice is typically accompanied by an increase in physical space, which may explain the reduced lying time (i.e., more alert and active) during weaning in pair housed compared to individually housed calves ( Chua et al, 2002 ; Overvest et al, 2018 ). Other studies found no differences in lying time over 5 wk during winter and summer months but found that paired calves offered two outdoor hutches chose to lie together in a single hutch ( Wormsbecher et al, 2017 ). Pair housed and individually housed calves in this study were reported to make similar use of the indoor and outdoor space ( Wormsbecher et al, 2017 ).…”
Section: Short- and Long-term Effects Of Conventional Raising Under Rmentioning
confidence: 99%
“…Other studies found no differences in lying time over 5 wk during winter and summer months but found that paired calves offered two outdoor hutches chose to lie together in a single hutch ( Wormsbecher et al, 2017 ). Pair housed and individually housed calves in this study were reported to make similar use of the indoor and outdoor space ( Wormsbecher et al, 2017 ).…”
Section: Short- and Long-term Effects Of Conventional Raising Under Rmentioning
confidence: 99%